Effectiveness of Rotavirus Vaccine in Reducing Hospital Admissions for Acute Diarrhea in Children Under 5 years of Age - Sehar Ansari, Shahjahan Anwar, Ahmad Yar, Sana Jamil, Sobia Shah Alam, Aamir Sohail, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Rotavirus is a leading cause of acute diarrhea among children under five, often resulting in hospital admissions and increased healthcare burden. Objective: To evaluate the effectiveness of the rotavirus vaccine in reducing hospital admissions, disease severity, and clinical complications associated with acute diarrhea in children under five years of age. Methods: This comparative observational study was conducted at The Children's Hospital Lahore from March 2023 to August 2023. A total of 95 pediatric patients under the age of five were included in this study. Patients with acute diarrhea defined as the sudden onset of three or more loose or watery stools within 24 hours, lasting less than 14 days were included in the study. The sample included both male and female children across various age groups within the under-five population. Results: Vaccinated children exhibited significantly lower rates of severe dehydration (21.2%) compared to unvaccinated children (44.2%). The average duration of hospital stay was shorter in the vaccinated group (2.3 ± 1.1 days vs. 3.8 ± 1.5 days). Complete recovery within 48 hours was higher among vaccinated children (88.5% vs. 60.5%). The unvaccinated group had a higher need for IV rehydration and accounted for all tertiary care referrals. The relative risk of severe outcomes in unvaccinated children ranged from 1.65 to 3.36 depending on the outcome measured. Conclusion: It is concluded that the rotavirus vaccine is effective in significantly reducing the severity and hospital burden of acute diarrhea in children under five. These findings support the continued inclusion and timely administration of rotavirus vaccines in national immunization programs. Keywords: Rotavirus, Acute Diarrhea, Vaccination, Hospitalization, Vaccine Effectiveness